COMPARATIVE STUDY BETWEEN THE MAIN CHARACTER DEVELOPMENT IN THE NOVEL “THE LITTLE PRINCE” AND “THE RETURN OF THE YOUNG PRINCE” - Alkausar, Alkausar; Burhamzah, Muftihaturrahmah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to compare the pattern of the hero’s journey theory in the novel The Little Prince by Antoine de Saint-Exupery with the novel The Return of the Young Prince by A.G. Roemmers. To obtain data from this analysis, the researcher used a qualitative method with a structuralism approach. The researcher read The Little Prince novel with the number of pages consisting of 101 pages and then read the Return of the Young Prince novel which consists of 108 pages. The types of stages from the hero’s journey theory by Campbell (1987) are divided into 12 parts consisting of the ordinary world, the call to adventure, refusal of the call, meeting the mentor, crossing the threshold, tests, allies, enemies, approach to the inmost cave, ordeal, reward, the road back, resurrection and return with the elixir. The result of this thesis found that the use of the hero’s journey theory can be traced from the books in the forms of 34 extracts, with the Little Prince book consisting of 19 extracts and the Return of the Young Prince consisting of 15 extracts.